Deep Learning Applications 2021
DOI: 10.5772/intechopen.96354
|View full text |Cite
|
Sign up to set email alerts
|

Material Classification via Machine Learning Techniques: Construction Projects Progress Monitoring

Abstract: Nowadays, the construction industry is on a fast track to adopting digital processes under the Industrial Revolution (IR) 4.0. The desire to automate maximum construction processes with less human interference has led the industry and research community to inclined towards artificial intelligence. This chapter has been themed on automated construction monitoring practices by adopting material classification via machine learning (ML) techniques. The study has been conducted by following the structure review app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Davis et al designed and described a deep CNN to identify seven typical Construction and Demolition Waste (C&DW) classi cations using digital images of waste deposited in a construction site bin [26]. Alaloul and Qureshi used an ANN model to classify some construction materials [5]. Accuracy:…”
Section: Background and Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Davis et al designed and described a deep CNN to identify seven typical Construction and Demolition Waste (C&DW) classi cations using digital images of waste deposited in a construction site bin [26]. Alaloul and Qureshi used an ANN model to classify some construction materials [5]. Accuracy:…”
Section: Background and Related Workmentioning
confidence: 99%
“…Although there are several studies conducted in the area of material classi cation, the literature review reveals that there are some shortcomings that need to be addressed. Some of the previous studies were restricted to just one speci c material [10-13, 19, 20, 25] or a limited number of material categories [5,6,16,17,21,22]. Furthermore, some studies employed tiny datasets, that is to say, they contained few images [13].…”
Section: %mentioning
confidence: 99%
See 2 more Smart Citations
“…The studies found photogrammetry, computer vision and ML as popular technologies for project progress and productivity monitoring. However, traditional procedures still have been adopted for various monitoring activities (Qureshi et al , 2022a; Alaloul and Qureshi, 2021).…”
Section: Introductionmentioning
confidence: 99%